2012
DOI: 10.5007/1980-0037.2012v14n6p738
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação específica no judô: uma revisão de métodos

Abstract: -The aim of this study was to analyze the judo specific tests present in the literature, including the variables obtained from these and their use as performance markers in judo matches. To develop of this study we considered original articles indexed from 1990 to 2011, using electronic data bases Scopus ® , SciELO ® , ScienceDirect ® (Elsevier) and PubMed ® . The keywords used for research were: judo, performance, aptitude tests and their combinations. After analyzing the articles deemed eligible, we elected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 23 publications
0
10
0
6
Order By: Relevance
“…Some authors emphasize the importance of carrying out the hip techniques with speed, but do not consider the different heights of the opponent 7,14 . No studies were found relating the speed of application with the throwing efficiency of the technique in judokas of different statures, or even at different throwing stages and in different judo techniques, which represents the need for research and information on these variables and their relation to the performance of judokas.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors emphasize the importance of carrying out the hip techniques with speed, but do not consider the different heights of the opponent 7,14 . No studies were found relating the speed of application with the throwing efficiency of the technique in judokas of different statures, or even at different throwing stages and in different judo techniques, which represents the need for research and information on these variables and their relation to the performance of judokas.…”
Section: Discussionmentioning
confidence: 99%
“…Cada modalidade esportiva de combate exige características morfofuncionais especificas(1) e modalidades de domínio (agarre) como o judô (JD) e o jiu-jitsu (JJ), apresentam algumas características muito próximas como a espacialidade/distância e ação motora (2,3), principalmente, no que se refere à execução de movimentos de agarrar, empurrar e imobilizar em curto espaço (3,4). Tanto o JD quanto o JJ, exigem força e flexibilidade como componentes físicos fundamentais para o êxito esportivo (5)(6)(7)(8)(9).…”
Section: Introductionunclassified
“…Em termos de desempenho, o JD caracterizase por esforço predominantemente do tipo intermitente, exigindo, também, habilidades corporais mais complexas (tempo de reação, memória motora, descontração diferencial, propriocepção) e de alta intensidade, aliadas a uma excelente tática de luta (10). Assim, a demanda fisiológica do JD é muito grande, pois envolve solicitações energéticas e neuromusculares amplas e em constantes mudanças, requerendo para isso uma boa combinação de aptidão aeróbia e anaeróbia e de força e flexibilidade (7).…”
Section: Introductionunclassified
“…O judô, como tantos outros esportes, dispõe de uma associação variada de capacidades físicas, além de pontos técnicos, táticos e psicológicos 6 . Suas técnicas seguem o princípio de máxima eficiência com o mínimo de esforço, baseiam-se em princípios biomecânicos que envolvem a aplicação de torque, estabilidade e equilíbrio nos momentos de inércia, centro de massa e utilização das alavancas 7 .…”
Section: Introductionunclassified